The Effect of Utilitarian, Hedonic, and Social Values on Behavioral Outcomes through Consumer Trust - Beby Karina Fawzeea Sembiring; Endang Sulistya Rini; Yeni Absah; Yossie Rossanty (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Live streaming e-commerce is rapidly transforming digital retail, yet the psychological drivers of consumer behavior in emerging markets like Indonesia. This study investigates consumer behavior in Indonesia’s live streaming e-commerce by examining how utilitarian, hedonic, and social values shape trust toward products and streamers, ultimately driving purchase intention and consumer engagement. Using the theory of consumption values integrated with trust-based models, data from 350 active live commerce consumers were analyzed with PLS-SEM via SmartPLS 4.0. The findings reveal that utilitarian, hedonic, and social values significantly enhance trust, which in turn strongly predicts purchase intention and consumer engagement. The model explains 52.5% of trust, 33.2% of purchase intention, and 21.8% of engagement variance, highlighting trust’s mediating role in linking consumption values to behavioral outcomes. The results emphasize the need for live commerce strategies that combine efficiency, entertainment, and community to cultivate trust, thereby boosting both immediate sales and long-term engagement. The study offers original contributions by being the first comprehensive empirical test in Indonesia applying consumption values and trust frameworks in live commerce.